Development of functional variability during the motor learning process of a complex cyclic movement - Hamacher, S.; Zech, A. (Journal of Biomechanics, 2018)
Traditionally, movement variability is considered an indicator for sensorimotor malfunctioning. However, functional movement variability is also a result of compensation mechanisms e.g. to account for prior movement deviations and is, therefore, crucial for stable movements. The aim of this study was to analyze functional variability during motor learning of a complex cyclic task.